2012
DOI: 10.5625/lar.2012.28.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Functions and physiological roles of two types of estrogen receptors, ERα and ERβ, identified by estrogen receptor knockout mouse

Abstract: Estrogens, a class of steroid hormones, regulate the growth, development, and physiology of the human reproductive system. Estrogens also involve in the neuroendocrine, skeletal, adipogenesis, and cardiovascular systems. Estrogen signaling pathways are selectively stimulated or inhibited depending on a balance between the activities of estrogen receptor (ER) α or ERβ in target organs. ERs belong to the steroid hormone superfamily of nuclear receptors, which act as transcription factors after binding to estroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(120 citation statements)
references
References 56 publications
3
114
0
3
Order By: Relevance
“…Estrogens exert their cellular effect via estrogen receptors scattered throughout whole male reproductive tract. It was reported that estrogen signaling is depended upon a balance between ERa and ERb activities [11]. In this way, decreased estradiol level can affect expression of estrogen receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estrogens exert their cellular effect via estrogen receptors scattered throughout whole male reproductive tract. It was reported that estrogen signaling is depended upon a balance between ERa and ERb activities [11]. In this way, decreased estradiol level can affect expression of estrogen receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The aromatase transcript was detected in pachytene and late spermatocytes, spermatids [9] and spermatozoa [10]. Androgens and estrogens exert their cellular effects via steroid receptors (ARs and ERs, respectively) of the nuclear receptor superfamily and act as ligand-dependent transcription factors [11]. After the binding of androgens, ARs undergo a conformational change, dimerization, translocation to the cell nucleus and binding to specific DNA sequence, thus modulating expression of target genes [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have proved that not only androgens have important functions in the adult male reproductive organ, but also estrogen and its receptors are essential for normal fertility in the male. Androgen and estrogen exert their cellular effects via steroid receptors (ARs and ERs, respectively) of the nuclear receptor superfamily and act as ligand-dependent transcription factors [26]. After the binding of androgens, ARs undergo a conformational change, dimerization, translocation to the cell nucleus and binding to specific DNA sequence, thus modulating expression of target genes [27].…”
Section: Introductionmentioning
confidence: 99%
“…These hormonal fluctuations clearly indicated towards a disruption in the pituitary-adrenal-testicular axis. Thereof, it is suggested that these hormones might play a crucial role in the development and progression of oral cancer [26].…”
Section: Effect Of Sex Hormones On Cancer Developmentmentioning
confidence: 99%